2016
DOI: 10.1371/journal.pone.0164041
|View full text |Cite
|
Sign up to set email alerts
|

The Ser82 RAGE Variant Affects Lung Function and Serum RAGE in Smokers and sRAGE Production In Vitro

Abstract: IntroductionGenome-Wide Association Studies have identified associations between lung function measures and Chronic Obstructive Pulmonary Disease (COPD) and chromosome region 6p21 containing the gene for the Advanced Glycation End Product Receptor (AGER, encoding RAGE). We aimed to (i) characterise RAGE expression in the lung, (ii) identify AGER transcripts, (iii) ascertain if SNP rs2070600 (Gly82Ser C/T) is associated with lung function and serum sRAGE levels and (iv) identify whether the Gly82Ser variant is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 40 publications
(61 reference statements)
2
36
0
Order By: Relevance
“…A reductionist RAGE recombinant cell model was used to study the function effects of the different alleles on the same genetic background and it was shown that the Ser82 variant of the receptor resulted in lower levels of secretion of soluble RAGE, demonstrating that the specific variant has functional consequences . Rather counterintuitively, serum or plasma levels of sRAGE in COPD patients are lower compared to controls.…”
Section: Translational Approaches: Gwas To Functionmentioning
confidence: 94%
See 2 more Smart Citations
“…A reductionist RAGE recombinant cell model was used to study the function effects of the different alleles on the same genetic background and it was shown that the Ser82 variant of the receptor resulted in lower levels of secretion of soluble RAGE, demonstrating that the specific variant has functional consequences . Rather counterintuitively, serum or plasma levels of sRAGE in COPD patients are lower compared to controls.…”
Section: Translational Approaches: Gwas To Functionmentioning
confidence: 94%
“…AGER mRNA is also expressed in the foetal lung, with increasing levels across the pseudoglandular and canalicular stages of human lung development. This finding correlated with protein expression during lung development . The study also showed that there was an association between rs2070600T and higher FEV 1 and FEV 1 /FVC as well as providing evidence that individuals with the Ser82 variant had significantly lower levels of serum sRAGE compared to Gly82 genotype individuals …”
Section: Translational Approaches: Gwas To Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…sRAGE is a short, soluble isoform of RAGE, and putative "decoy" receptor. Because it lacks the intracellular and cytoplasmic domains required for signaling, sRAGE is predicted to protect against inflammation and RAGE-dependent cellular stress by sequestering RAGE ligands and preventing their engagement of the full-length, transmembrane RAGE [72,73]. Thus, in humans bearing this SNP, lower sRAGE concentrations may directly amplify ligand burden and availability for signal transduction through full-length RAGE.…”
Section: Consequences Of Rage Signal Transductionmentioning
confidence: 99%
“…Additional work is required to link these loci to pathophysiology. Functional studies on GWAS loci involving HHIP ,12 13 FAM13A ,14 HTR4 ,15 AGER 16 and IREB2 17 have already provided important insights into the biological mechanisms for genetic determinants of COPD and/or lung function.…”
mentioning
confidence: 99%